Peer Coaching - Ladyshewsky, R.; Ladyshewsky, Rick (SAGE Publications Limited, 2018)
This book provides a wide-ranging guide to the complex, multidisciplinary area of coaching, helping trainees to find comprehensive answers to their coaching questions.